Current state and open issues of priming onion seeds - A. V. Yanchenko; A. F. Bukharov; A. Yu. Fedosov; M. I. Ivanova; A. M. Menshikh; S. V. Belova (Овощи России, 2024)
Relevance. In the context of climate change, onion cultivation has become a challenge and innovative solutions are needed to support breeders and seed producers as well as farmers, starting with critical issues of seed quality. Seed priming successfully improves seed viability, which leads to rapid and uniform germination and emergence of onion seedlings.Results. Priming onion seeds can improve viability, especially under unfavorable conditions such as low/high temperatures, reduced water availability and salinity. It is a simple, low-cost and low-risk intervention that can be a useful technology for farmers and have a positive impact on their livelihoods by increasing the rate of seed germination, increasing the rate of plant development, reducing harvest time and increasing yields. Although this method is common for radish, tomato, carrot and cabbage seeds, this method is less popular for onions. This review provides an up-to-date picture of the scientific and technological advances that have contributed to increasing seed germination and vigor in onion plants to date. For large-scale commercial use, optimal priming methods and conditions tailored to different varieties or seed lots will require further extensive experimental work. It cannot be denied that seed priming technology is characterized by ease of operation, low cost and high practical value in industrial and market contexts. It can be foreseen that this technology will have wider prospects in agricultural production and green building. In addition, seed priming can effectively restore or enhance seed viability and ensure successful retention of germplasm resources and subsequent development, especially for onion seeds that rapidly lose viability.